This seat of Mars: war and the British Isles; 1485 - 1746 - Carlton, Charles (Yale Univ. Press, 2011)
Early Tudor Warfare, 1485-1558 -- Give me spirit: joining and training -- This happy breed of men: Elizabethan Warfare, 1558-1603 -- Why men fought -- Those were Golden Days: early Stuart Warfare, 1603-1639 -- Low intensity combat: campaigning -- All diseas'd: Civil Wars and Commonwealth: events, 1638-1660 -- Talk you of killing: Civil Wars and commonwealth: impact, 1638-1660 -- High intensity combat: battles and sieges -- Restoration to glorious revolution, 1660-1688 -- The peril of the waters: war at sea -- Let slip the dogs of war: after the glorious revolution 1688-1746 -- The hurlyburly's done: the aftermath of combat